A novel pinch-based method for process integration and optimization of Kalina cycle. (1st April 2020) - Zhou, Congcong; Zhuang, Yu; Zhang, Lei; Liu, Linlin; Du, Jian; Shen, Shengqiang
Graphical abstract: Highlights: A novel pinch-based mathematical model is developed. Process integration and optimization of Kalina Cycle are conducted simultaneously. The model allows for non-isothermal phase transition of working fluid. Multiple Kalina Cycles are integrated with process streams. A 4.13 percentage point decrease in the efficiency penalty for carbon capture process. Abstract: Low-and-medium waste heat utilization is crucial for alleviating energy dilemma and carbon dioxide emissions in industrial plants. Although Organic Rankine Cycle (ORC) has made significant advances in waste heat recovery, other equally important thermodynamic ways to recover waste heat such as Kalina Cycle (KC) have not been fully explored. In this study, a novel pinch-based mathematical model is developed for process integration and optimization of Kalina Cycle. The model performs heat integration with variable heat capacities and enables the modifications of KC simultaneously, in a bid for generating maximum net power output without increasing the amount of hot utility. The proposed model allows for non-isothermal phase transition of working fluid and can be extended to handle multiple Kalina Cycles combined with process integration, thus enhancing waste heat recovery efficiency. The effectiveness of the proposed method is verified by a well-studied example from literature, in which the net power output is increased by 12.2% compared to the results using existing literature approaches. Furthermore, the developed model has been successfully applied to the post-combustion carbon capture process, where proper integration of process and Kalina Cycle leads to a 15.8% increase in net power output and a 4.13 percentage point decrease in the efficiency penalty.